Difficulties Facing the Professional Practice of Social Work in Achieving Social Inclusion for Persons with Intellectual Disabilities - Eid, Dr. Adel Ezzat Mohammed (Migration Letters, 2024)
The focus on human beings and their care is one of the important issues for all countries in the world, as human beings represent the nucleus of development, and their care is one of the most important criteria by which the progress of nations is measured (Ajaj, et al., 2022). The current century has witnessed significant interest in the care of people with disabilities, and social care for the disabled has become one of the leading programs in both advanced and developing countries. The aim is to consciously plan to bring about the intended change and achieve compatibility between the individual’s performance of his roles and social functions and his environment in which he lives. The disabled individual should realize that they possess immense abilities and potentials if they are trained, guided, and rehabilitated to become productive individuals like others (Ghubari, 2013, p.8) The issue of disability is a multidimensional problem that does not only affect the disabled child but also extends its effects to the family and society. These effects vary depending on the type and degree of disability. The more severe the disability, the greater the obstacles to social integration, in addition to the numerous economic and social consequences of disability (Annual Report of the Disability Care Authority, 2020).